Agreement between the Caribbean Communities (CARICOM) and the Government of the Republic of Venezuela on trade and investment (CCS GeorgetownGY, 1993)
States the expressed objective of the Agreement and the means through which it would be achieved. Looks at specific aspects of the agreement such as its elements; the Joint Council and Advisory Group; trade liberalisation; rules of origin; and harmonized commodity description and coding system.
DC